2003
DOI: 10.1046/j.1365-2923.2003.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the challenge of prescribing and administering medicines safely: structured teaching and assessment for final year medical students

Abstract: Structured teaching provided an effective and acceptable method of teaching the medicines management skills needed in the PRHO year. The structured approach complemented variable precourse clinical experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 3 publications
6
66
0
1
Order By: Relevance
“…Prescribing as a whole Eight of the trials used educational interventions that were directed at a broad range of prescribing tasks from drug history to choosing a treatment and writing the prescription [14][15][16][17][18][19][20][21]. Six trials were based on the World Health Organization (WHO) Good Prescribing Guide intervention [14][15][16][17][18][19], whereas two trials used their own in-house intervention [20,21].…”
Section: Controlled Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prescribing as a whole Eight of the trials used educational interventions that were directed at a broad range of prescribing tasks from drug history to choosing a treatment and writing the prescription [14][15][16][17][18][19][20][21]. Six trials were based on the World Health Organization (WHO) Good Prescribing Guide intervention [14][15][16][17][18][19], whereas two trials used their own in-house intervention [20,21].…”
Section: Controlled Trialsmentioning
confidence: 99%
“…Six trials were based on the World Health Organization (WHO) Good Prescribing Guide intervention [14][15][16][17][18][19], whereas two trials used their own in-house intervention [20,21].…”
Section: Controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequence of this change has been low visibility within the curriculum, with too many drugs being introduced within clinical modules, no clear prioritization (and occasional disputes) as to core learning about drugs, a lack of coordination between basic science and clinical teaching, and no source of concise information about the core drugs. Objective feedback from Post-Registration House Officers in Edinburgh has shown that they felt inadequately prepared to prescribe, and similar concerns have been expressed elsewhere by students and teachers [18,19,21,22]. The GMC published a revised version of Tomorrow's Doctors [23] in July 2002, which provided rather more direction about teaching and assessment of therapeutics [24].…”
Section: Related Issues and Resources From A Medical Perspectivementioning
confidence: 92%
“…13 In contrast, a UK study showed that five additional tutorials led by pharmacists produced significant improvements in five of seven OSCE stations covering prescribing skills that had been taught. 14 The weakness of these two trials stems from lack of randomisation or matching of groups -the intervention students and controls could have had different baseline skills and attitudes.…”
Section: Cme Clinical Pharmacologymentioning
confidence: 99%